Multi-agent systems for education and interactive entertainment : design, use and experience - Beer, M. D. (Martin D.); Fasli, Maria; Richards, Debbie (Hershey PA : Information Science Reference, 2011)
'This book presents readers with a rich collection of ideas from researchers who are exploring the complex tradeoffs that must be made in designing agent systems for education and interactive entertainment'--Provided by publisher.
Includes bibliographical references (p. 273-299) and index.
Keywords: Multiagent systems -- Congresses; Instructional systems -- Congresses; Computer science -- Study and teaching -- Congresses